Total Versus Free Placental Growth Factor Levels in the Pathogenesis of Preeclampsia - Lecarpentier, Edouard; Zsengellér, Zsuzsanna K.; Salahuddin, Saira; Covarrubias, Ambart E.; Lo, Agnes; Haddad, Bassam; Thadhani, Ravi I.; Karumanchi, S. Ananth (Hypertension (Dallas, Tex. 1979), 2020)
Elevated circulating sFLT-1 (soluble fms-like tyrosine kinase) and low levels of its ligand, PlGF (placental growth factor), are key characteristics of preeclampsia. However, it is unclear if the low levels of plasma PlGF noted during preeclampsia are due to decreased placental production of PlGF or due to binding of PlGF by increased circulating sFLT-1. Here, we describe a biochemical procedure to dissociate PlGF-sFLT-1 complex ex vivo and when used in conjunction with an immunoassay platform, demonstrate a method to measure total and free PlGF in human blood samples. Using this method, we noted that plasma free PlGF levels were significantly lower in preeclampsia (N=22) than in nonhypertensive controls (N=24; mean, 314 versus 686 pg/mL, P<0.05), but total PlGF levels were not different (mean, 822 versus 800 pg/mL, P=0.49). In contrast, total sFLT-1 levels were significantly higher in preeclampsia than in nonhypertensive controls (mean, 16 957 versus 3029 pg/mL, P<0.01) and sFLT-1 levels correlated with bound PlGF levels (bound PlGF=total PlGF−free PlGF) in these samples (r2=0.68). We confirmed these findings in an independent cohort of subjects (N=49). Furthermore, we did not detect any difference in PlGF mRNA by quantitative polymerase chain reaction or in PlGF protein expression by immunohistochemistry in preeclamptic placentas when compared with nonhypertensive controls. In contrast, sFLT-1 mRNA and protein levels were upregulated in placentas from women with preeclampsia. Taken together with prior studies, our results provide evidence that decrease in circulating PlGF noted during preeclampsia is largely mediated by excess circulating sFLT-1.